Catalytic Partial Oxidation of Cyclohexane by Bimetallic Ag/Pd Nanoparticles on Magnesium Oxide. Issue 49 (16th August 2017) - Liu, Xi; Conte, Marco; He, Qian; Knight, David W.; Murphy, Damien M.; Taylor, Stuart H.; Whiston, Keith; Kiely, Christopher J.; Hutchings, Graham J.
Abstract: The liquid‐phase oxidation of cyclohexane to cyclohexanol and cyclohexanone was investigated by synthesizing and testing an array of heterogeneous catalysts comprising: monometallic Ag/MgO, monometallic Pd/MgO and a set of bimetallic AgPd/MgO catalysts. Interestingly, Ag/MgO was capable of a conversion comparable to current industrial routes of approximately 5 %, and with a high selectivity (up to 60 %) to cyclohexanol, thus making Ag/MgO an attractive system for the synthesis of intermediates for the manufacture of nylon fibres. Furthermore, following the doping of Ag nanoparticles with Pd, the conversion increased up to 10 % whilst simultaneously preserving a high selectivity to the alcohol. Scanning transmission electron microscopy and energy dispersive spectroscopy of the catalysts showed a systematic particle‐size‐composition variation with the smaller Ag–Pd nanoparticles being statistically richer in Pd. Analysis of the reaction mixture by electron paramagnetic resonance (EPR) spectroscopy coupled with the spin‐trapping technique showed the presence of large amounts of alkoxy radicals, thus providing insights for a possible reaction mechanism. Abstract : Trap my spin ! AuPd/MgO nanoparticles were found to be active for the selective oxidation of cyclohexane to cyclohexanol and cyclohexanone. EPR spectroscopy study coupled with the spin‐trapping technique showed the presence of large amounts of alkoxy radicals, thus providing insights for a possible reaction mechanism (see figure).